2022
DOI: 10.1155/2022/9443884
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Knowledge and Information Needs about Isotretinoin Therapy Use in Jordan

Abstract: Background. Despite being the first-line treatment for severe or moderate acne, isotretinoin has several serious side effects that necessitate the evaluation of patients’ knowledge about isotretinoin side effects and its proper use. Objective. The current study aim was to explore information needs about isotretinoin by evaluating patients’ knowledge about the appropriate use of isotretinoin and its associated side effects. Methods. In addition to the sociodemographic variables, a validated online questionnaire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…It underscores the importance of monitoring and addressing ocular changes during isotretinoin treatment to ensure the well-being and visual health of the patients. This supports the findings of Jarab et al (2022) [ 16 ], who found a comparable percentage of participants experiencing worsened or new eye symptoms prior to isotretinoin treatment.…”
Section: Discussionsupporting
confidence: 91%
“…It underscores the importance of monitoring and addressing ocular changes during isotretinoin treatment to ensure the well-being and visual health of the patients. This supports the findings of Jarab et al (2022) [ 16 ], who found a comparable percentage of participants experiencing worsened or new eye symptoms prior to isotretinoin treatment.…”
Section: Discussionsupporting
confidence: 91%
“…The duration of treatment with isotretinoin, as recommended by the AAD, is minimally 3 months, up to the maximum duration of 6 months. In this study, 25% of participants had used isotretinoin for an improper duration of treatment, which is lower than the findings of other studies; for example, the improper duration reported was 35% in a study conducted in Quebec City study, 10 68% of a Saudi female college students’ students’ study, 14 and 44.7% in the Jordan University of Science and Technology study, 15 all had undergone a duration of therapy longer than 6 months. 1 , 12 , 13 Adherence to the treatment duration is essential for the efficacy and prevention of long-term damage and complications with longer treatment durations, such as permanent loss of eyesight, erectile dysfunction, and loss of libido.…”
Section: Discussioncontrasting
confidence: 67%
“… 2 For example, in a Jordanian study, 98.4% of patients were informed about the contraindication of blood donation, and 75.4% were informed about the importance of hydration and sunblock, respectively. 15 Also, in a study performed in the western region of Saudi Arabia, 84.6% of patients were informed about isotretinoin side effects by physicians and pharmacists. 18 The low adherence in clinical practice regarding patient counseling and educations is due to the lack of pharmacy practice laws that enforce patient counseling as not only ethical responsibility for practitioners but also a legal one that is required by laws.…”
Section: Discussionmentioning
confidence: 99%
“…Isotretinoin has the potential to effectively treat acne, but there are many controversial opinions about this medication that are often based on insufficient data [ 15 ]. Literature indicates that there is a low level of awareness among users about the possible side effects of isotretinoin, the duration of treatment, and some instructions about the use of isotretinoin [ 16 ]. A study showed that there are no specific criteria to determine the appropriate dose of low-dose isotretinoin [ 17 ].…”
Section: Introductionmentioning
confidence: 99%